Health Information Seeking Behavior and Health Information Preferences Among Ethnically and Socioeconomically Diverse Patients and Communities: A Qualitative Study - Bryn Hummel; Dinah L. van Schalkwijk; Paula M. C. Mommersteeg; Irene G. M. van Valkengoed (Journal of Primary Care & Community Health)
Introduction: Early recognition of ischemic heart disease (IHD) is important, yet, delays still occur due to low symptom recognition. Accessible information may improve symptom recognition, however, it is unclear how information should be provided to reach different populations. Hence, we studied health information seeking behavior (HISB) and preferences, in ethnically-diverse women and men in the Netherlands. Methods: We conducted 31 patients interviews, seven key figure interviews and one focus group with key figures (community leaders and physicians), and eight focus groups with non-patients (N = 44) about HISB and health information preferences. We thematically analyzed the data using inductive coding. Results: We found minimal variation in HISB, as most patients did not seek information about symptoms. Participants required information about cardiac symptoms, risk factors, when to seek care, prevention, and navigating the Dutch healthcare system. Several information provision strategies emerged, with preferences varying somewhat across ethnic groups and age groups. Ethnic minority participants described a preference for culturally-sensitive community-based live information provision. Other strategies included media, social media, and native Dutch participants mentioned public spaces and healthcare settings. Conclusion: HISB was limited in this ethnically-diverse population. Different strategies may be employed to promote symptom recognition, particularly co-created culturally-sensitive interventions.